Referral System of the BPJS Patient at the Halmahera Community Health Center Semarang City - Aulia Putri Kafrawi; Eliyah Eliyah; Retnowati Retnowati (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
Implementation of SISRUTE in Health Centers needs to be a priority in the implementation of RME, there is a discrepancy between the implementation of SISRUTE in Halmahera Health Center and the applicable provisions. This study to describe the implementation of SISRUTE in Halmahera Health Center, Semarang City from the aspects of human, organization, technology, net-benefit. This research using the HOT-Fit method, data collection through observation and interviews. Human aspect, the owner of the SISRUTE account is a doctor but is operated by nurses and midwives on duty, there has been no training to develop the ability to use SISRUTE for HR other than the account owner. Organization aspect, shows the existence of SOP and Decree of the Head of Health Center regarding the delegation of authority to use SISRUTE accounts in Health Centers. The technology aspect of SISRUTE has not been bridged with other Health Information Systems, data integration has not been created between Health Centers and Hospitals, so that referral files are still manual and require re-entry time at the Hospital. Net-benefit aspect, SISRUTE has not been a priority for referral applications so that speed, effectiveness and efficiency cannot be measured.